2020
DOI: 10.1039/d0tc01674h
|View full text |Cite
|
Sign up to set email alerts
|

Direct solid-state nucleation and charge-transport dynamics of alkali metal-intercalated M2Mo6S6 (M = K, Rb, Cs) nanorods

Abstract: Microwave-assisted solid-state heating has been employed to induce anisotropic nucleation of M2Mo6S6 (M = K, Rb, Cs) nanorods without a template for the first time, and interfacial charge-transport properties of these rods are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…We have this potential testbed in 2D cross-dimensional heterostructures ( vide infra ). However, we must establish surface structure–reactivity relationships taking into account the surface and bulk composition which can help accelerate discovery and design ( Perryman et al., 2020a ; Ortiz-Rodríguez et al., 2020 ). Where 2D vdW structures are posited to afford bidentate coordination environments ( Figure 1 A) for catalytically important intermediate species in the CO2RR as an alternative to potentially less favorable monodentate structures ( Figure 1 B), it has been shown that the ternary composition of 3D chalcogenides like Chevrel phases affords a similar level of control over adsorbate binding ( Liu et al., 2010 ; Liu and Liu, 2015 ).…”
Section: Metal Chalcogenides As Electrocatalysts For Co 2 Reductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have this potential testbed in 2D cross-dimensional heterostructures ( vide infra ). However, we must establish surface structure–reactivity relationships taking into account the surface and bulk composition which can help accelerate discovery and design ( Perryman et al., 2020a ; Ortiz-Rodríguez et al., 2020 ). Where 2D vdW structures are posited to afford bidentate coordination environments ( Figure 1 A) for catalytically important intermediate species in the CO2RR as an alternative to potentially less favorable monodentate structures ( Figure 1 B), it has been shown that the ternary composition of 3D chalcogenides like Chevrel phases affords a similar level of control over adsorbate binding ( Liu et al., 2010 ; Liu and Liu, 2015 ).…”
Section: Metal Chalcogenides As Electrocatalysts For Co 2 Reductionmentioning
confidence: 99%
“…Beyond simply controlling local coordination via compositional modification in flexible 3D chalcogenide frameworks, it is also understood—albeit underexplored—that even morphological changes in 3D systems can introduce profound changes in locally observed electric fields for CO 2 reduction intermediates ( Gao et al., 2012 , 2020 ). This strongly motivates the exploration of additional synthetic techniques that will enable control over particle morphology on well-defined chalcogenide compositions ( Perryman et al., 2020a ), similar to the established hydrothermal and solvothermal routes that have been employed for metal oxide nanoparticle catalysts for thermal CO 2 reduction ( Jiang et al., 2020a ; Liang et al., 2014 ).…”
Section: Metal Chalcogenides As Electrocatalysts For Co 2 Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously reported results of computational surface energy modeling for K2Mo6S6 <010>, <110>, and <001> surfaces 8. …”
mentioning
confidence: 99%